Formulation and evaluation of the antimalarial N-89 as a transdermal drug candidate. (April 2023) - Aly, Nagwa S.M.; Matsumori, Hiroaki; Dinh, Thi Quyen; Sato, Akira; Miyoshi, Shin-Ich; Chang, Kyung-Soo; Yu, Hak Sun; Kim, Hye-Sook
Abstract: The discovery of new effective and safe antimalarial drugs is mandatory. In this report, we formulate and evaluate transdermal (td) 1, 2, 6, 7-tetraoxaspiro[7.11]nonadecane (N-89) using the Plasmodium berghei rodent malaria parasite in vivo model. The selected solvent for the ointment type of td N-89 was polyethylene glycol (PEG) [PEG400:PEG 4000 = 8:1 ( v / w )]. We tested different application areas of 4, 6, and 8 cm 2 on the shaved backs of mice. Pharmacokinetic (PK) analysis of N-89 parameters after a single 4 cm 2 transdermal application revealed that the Tmax was 2 h, the T1/2 was 1.9 h, and the AUC was 1951.1 ng . h/mL. More than 10 ng/mL of plasma concentration was maintained for 12 h. The ED50 values for the 4, 6, and 8 cm 2 application areas in a 4-day suppressive test were 18.9, 25.1, and 26.8 mg/kg, respectively. We additionally tested the cure effect of td N-89 in mice at a dose of 60 mg/kg, twice daily for 4 days at 0.2% parasitemia. Parasites disappeared following day 7 post-treatment in all td N-89 treated groups. Mice were cured without any parasite recurrence or dermal irritation. In conclusion, this study determined for the first time the PK parameters and effect of a new ointment type of td N-89. This suggests that transdermal treatment with N-89 is an effective and safe alternative route for the treatment of malaria, especially in children. Graphical abstract: Unlabelled Image Highlights: An ointment type of N-89 shows strong antimalarial activity in vivo . Plasma concentration of td N-89 of 10 ng/ml was maintained for 12 h in mice. Td N-89 is an effective and safe route for the treatment of malaria parasites.